Penerapan Water Safety Plans (WSP)-Komunitas dalam Penyediaan Air Minum Berbasis Masyarakat di Kelurahan Bangetayu Kulon Kecamatan Genuk Kota Semarang - Saura Olivia Effendi (Department of Urban and Regional Planning, Diponegoro University, 2013)
Water safety plan (WSP) is defined as a comprehensive approach to risk assessment and risk management approach to ensure the safety of drinking water supplies covers all stages in the supply of water, from the source to the customer with the health-based targets (Sam Godfrey and Guy Howard, 2004 and WHO, 2009). The concept developed by WSP includes four basi c elements, namely: WSP-Sources, WSP-Operator, WSP-Community, and WSP-Consumer. Implementation of WSP in Indonesia will focus on community WSP concept. The research approach used is a mixture of research approach (a combi nation of qualitative and quantitative). Pamsimas is a government program in a community-based compliance and water safety aimed at improving access to drinking water and sanitation for the poor rural and suburban areas. In February 2012, BPSPAMS Tirto Makmur Abadi Bangetayu Kulon Semarang City ranked first in the city of Semarang in 2012. Based on the above, the researchers wanted to examine whether the WSP-community concept has been applied in community-based drinking water supply by Pamsimas in Bangetayu Kulon village Genuk Subdistrict of Semarang. According to identification and analysis results, implementation of water supply by Pamsimas in Bangetayu Kulon village still not in accordance with the application of the community WSP concept. Pamsimas have not implemented security systems such as WSP concept, where new security measures are determined when the program is completed and the impact has been felt.